Conotruncal malformations and absent thymus due to a deleterious NKX2-6 mutation. Issue 4 (13th January 2014) - Ta-Shma, Asaf; El-lahham, Nael; Edvardson, Simon; Stepensky, Polina; Nir, Amiram; Perles, Zeev; Gavri, Sagui; Golender, Julius; Yaakobi-Simhayoff, Nurit; Shaag, Avraham; Rein, Azaria J J T; Elpeleg, Orly
Abstract : Background: Truncus arteriosus (TA) accounts for ∼1% of congenital heart defects. The aetiology of isolated TA is largely unknown but when occurring as part of a syndrome, it is mostly associated with chromosome 22q11 deletion. Vice versa, the most common congenital heart defects associated with chromosome 22q11 deletion are conotruncal malformations. In this study we investigated the cause of multiple conotruncal malformations accompanied by athymia in a consanguineous family. Methods and results: Whole exome analysis revealed a homozygous deleterious mutation in the NKX2-6 gene. Conclusions: NKX2-6 encodes a homeobox-containing protein which is expressed in mouse embryo at E8.0-E9.5 at the caudal pharyngeal arches and the outflow tract. A single missense mutation was previously implicated in the aetiology of familial isolated TA; however, null mice are entirely normal. The clear phenotype associated with a homozygous deleterious mutation in the present report, falls well within the spectrum of the cardiac defects seen in DiGeorge syndrome, is in agreement with NKX2-6 downstream location in the TBX1 signalling pathway and confirms NKX2-6 role in human cardiogenesis.